Metabolite profiling of saliva for the discrimination of Behcet’s disease, Sjögren’s syndrome, and recurrent aphthous stomatitis - Sooah Kim; Ming Zhang; Joong Kyong Ahn; Jiwon Hwang (PLoS ONE, 2026)
Oral manifestations can be the initial sign of systemic diseases such as Behcet’s disease (BD) and Sjogren’s syndrome (PSS). Their frequency and morphology vary widely, and recurrent aphthous stomatitis (RAS) often mimics BD ulcers, complicating differentiation on clinical grounds. Nonspecific aphthoid lesions are also seen in PSS. This study aimed to identify distinctive metabolic patterns in saliva that could discriminate BD, PSS, and RAS using global metabolite profiling. Saliva samples were collected from 43 patients (BD, n = 24; PSS, n = 10; RAS, n = 9) after fasting and abstaining from oral activities for at least 90 minutes. Gas chromatography-mass spectrometry (GC/MS) was employed for metabolite profiling. Principal component analysis (PCA) and hierarchical clustering analysis (HCA) were used to distinguish groups. Variable importance in projection (VIP) scores were calculated from partial least squares discriminant analysis (PLS-DA), and ANOVA was applied to compare metabolite abundance. Forty-two metabolites were identified and categorized into amino acids, organic acids, sugars, sugar alcohols, and others. PCA and HCA demonstrated clear dis-crimination among BD, PSS, and RAS. Metabolites with VIP > 1 included malonic acid sorbitol, pyroglutamic acid, aspartic acid, decanoic acid, hexadecenoic acid, and L-proline. Notably, malonic acid and aspartic acid were significantly elevated in BD compared to PSS and RAS, suggesting their diagnostic potential. Global salivary metabolite profiling by GC/MS provides distinct metabolic signatures enabling discrimination among BD, PSS, and RAS. This approach may enhance understanding of oral mucosal manifestations in systemic autoimmune diseases.